2006
DOI: 10.1097/01.fbp.0000189813.54178.e3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biasing the location of stimulus presentation, and the muscarinic cholinergic receptor antagonist scopolamine, on performance of a 5-choice serial reaction time attention task in rats

Abstract: A major purpose of the present studies was to determine the effects of varying the relative frequency, or bias, of stimulus presentation at different locations in a five-choice serial reaction time attention task. Training sessions were conducted in which the stimulus duration was held constant at 2 s and, initially, stimuli were presented with equal probability above each of the levers. During testing sessions, however, stimulus duration was either 0.2 or 2 s, and the frequency of presentation was varied amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 16 publications
1
7
1
Order By: Relevance
“…Similarly, scopolamine decreased workers’ choice of HR but had no significant effect on accuracy. This lack of effect on accuracy stands in contrast to some 5CSRTT literature [41] , [42] , and may be the result of additional training for the rCET animals and differences in dosing methodology [43] , [44] . Altogether, it appears that acetylcholine manipulations affect multiple subsystems, including those that underlie decision making, attention, and impulsivity.…”
Section: Discussioncontrasting
confidence: 65%
“…Similarly, scopolamine decreased workers’ choice of HR but had no significant effect on accuracy. This lack of effect on accuracy stands in contrast to some 5CSRTT literature [41] , [42] , and may be the result of additional training for the rCET animals and differences in dosing methodology [43] , [44] . Altogether, it appears that acetylcholine manipulations affect multiple subsystems, including those that underlie decision making, attention, and impulsivity.…”
Section: Discussioncontrasting
confidence: 65%
“…Scopolamine has been found to block long‐latency, long‐lasting depolarizing responses of thalamocortical neurons evoked by electrical stimulation of mesopontine cholinergic nuclei (Curró Dossi et al ., 1991). Systemic administration of scopolamine has consistently been shown to increase omissions for five choice serial reaction time tasks (5‐CSRTT) at doses around 0.25 µmol/kg (Jones & Higgins, 1995; Mizra & Stolerman, 2000; Lindner et al ., 2006; Shannon & Eberle, 2006) and to increase RT for other measures of visuomotor responding (Davidson et al ., 1999; Phillips et al ., 2000). Several of these studies have shown no effect of comparable doses of methyl scopolamine, providing evidence for a central site of action.…”
Section: Discussionmentioning
confidence: 99%
“…The DMN was originally characterized with "blocked" designs where data from active and passive conditions were averaged over multiple relatively longer periods and where activation was statistically greater during rest than during task conditions (Mazoyer et al 2001, Shulman et al 1997. Subsequent meta-analyses of PET (Mazoyer et al 2001, Shulman et al 1997 and fMRI data (Shannon & Eberle 2006) confirmed that across many materials (e.g., verbal and nonverbal), multiple modalities (e.g., visual and auditory), and many tasks, there was greater activation in the four core DMN regions during rest than during task performance.…”
Section: Dmn Definition and Anatomical Regionsmentioning
confidence: 99%